Penyuluhan dan Praktik Budidaya Tayurdapot untuk Kelompok Tani “Abdi Dalem Klebengan”, Kelurahan Kadipiro, Banjarsari, Surakarta - Sudadi Sudadi; Slamet Minardi; Ongko Cahyono; Vita Ratri Cahyani; Siti Maro'ah (Universitas Sebelas Maret, 2024)
Counseling and Practices of Tayurdapot Cultivation for Farmers Group “Abdi Dalem Klebengan”, Kadipiro Village, Banjarsari, Surakarta. Citizens association (RW) 17 as a partner in this community service activity is one of the RWs in Kelurahan Kadipiro, Banjarsari District, Surakarta City which has a farmer group, namely the Farmer Group (Poktan)